Imagining the Other: Mimetic Theory, Migration, Exclusionary Politics, and the Ambiguous Other - Regensburger, Dietmar; Wandinger, Nikolaus (innsbruck university press, 2023)
In July 2019, the Colloquium on Violence and Religion (COV&R) held its annual conference at the University of Innsbruck dealing with the challenges of global migration. Experts from many fields gathered to discuss the problem of migration, and to elucidate it with the help of mimetic theory. However, the migration theme can be read as part of a larger challenge: how do we perceive the other - the other who migrates from a foreign land, the other who thinks and behaves differently than "we" do, or the other who transcends this world altogether, and whom the religions call "God"? Aware that imagination is a mimetic process, the contributors to this volume try to illuminate different aspects of this complex entanglement, asking whom or what we mean by "the other": the stranger and migrant, the brother or sister, nature that envelops or defies us, the transcendent Other. The three parts of this book employ mimetic theory to analyze the imagination of the other and the challenges of migration, to illustrate the politics of migration, looking at particular problems and case studies, and to probe the imagination of the other between exclusion and adoration.